Barron's regents exams and answers. Biology, the living environment - Edwards, Gabrielle I.; Barron's Educational Series, inc. (Hauppauge, N.Y. : Barron's Educational Series, 2002)
A guide to preparing for the Biology Regents exam, a test required to meet the commencement standards of New York, featuring test-taking tips, study questions and answers, a glossary of prominent scientists and biological terms, previous Regents exams and answers, and self-appraisal charts.
Young Adult
Keywords: Biology -- Examinations, questions, etc; Examinations -- New York (State); Biology -- Examinations; Examinations -- New York (State)